Improvement of the emulsifying and oxidative stability of myofibrillar protein prepared oil-in-water emulsions by addition of zein hydrolysates. (February 2017) - Li, Yuanyuan; Kong, Baohua; Liu, Qian; Xia, Xiufang; Chen, Hongsheng
Graphical abstract: Highlights: Zein hydrolysates improve the emulsifying and oxidative stability of MP emulsions. Emulsions with 5 mg/mL ZH had a good ESI and low creaming index. The interfacial membrane in emulsions with ZH was more compact and more massive. The addition of ZH reduced the POV and TBARS of emulsions during storage. Abstract: This study investigated the effects of zein hydrolysate (ZH) on the improvement of the emulsifying and oxidative stability of oil-in-water (O/W) emulsions prepared by myofibrillar protein (MP). The emulsifying activity index (EAI) and emulsion stability index (ESI) increased with the increase of ZH concentrations. Emulsions with 5 mg/mL ZH had the highest ESI and ζ -potential, the smallest mean particle size, and the lowest creaming index ( p < 0.05). Confocal laser scanning microscopy (CLSM) observation proved that emulsions with ZH possessed relatively small oil droplets, especially emulsions with 5 mg/mL ZH, which were coincident with the results of droplet diameters and particle size distributions. The micrographs demonstrating the adsorption of ZH on the interfacial membrane of oil droplets in emulsions by CLSM also revealed that the interfacial membrane in emulsions with 5 mg/mL ZH were more compact and more massive than that those without ZH. The addition of ZH significantly reduced the peroxide values and thiobarbituric acid-reactive substances values ( p < 0.05) of emulsions during 10 days of storage. In general, our results revealed that the ZH promoted the adsorption of protein on the O/W interface and improved the emulsifying and oxidative stability of the MP O/W emulsion.